Microcontroller for a volumetric respirator - Martínez Martínez, A.; López Arriola, C. J.; Jiménez Alaniz, J. R. (Revista Mexicana de Ingenieria Biomedica, 1988)
A control system for a volumetric fan based on an Intel 8031 microcontroller is described. The characteristics of the system, the process of time and flow control, as well as the monitoring and alarm system are presented.